2018
DOI: 10.1007/s10100-018-0527-x
|View full text |Cite
|
Sign up to set email alerts
|

Pricing decisions in marketing channels in the presence of optional contingent products

Abstract: The technological developments observed in the last two decades contributed to the digitalization of products and the introduction of various mobile devices designed for the consumption of this digital content. Many online retailers launched their own mobile devices, which had a direct effect on their multi-product pricing strategies, but also an effect on the other channel members' pricing decisions (i.e., digital-content providers). In many industries, these developments resulted in switching from traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…It may come to price wars (using promotions) if networks decide that demand stimulation is only possible by lowering prices. In order to keep margins at a satisfactory level in such a situation, the significant changes in sales channels, price management, pricing mechanisms and promotions are needed [4]. They are the following:…”
Section: S Ect Io N I I E Nt R Ep Rene U Rs Hi P T Ra De and Service S Ecto Rmentioning
confidence: 99%
“…It may come to price wars (using promotions) if networks decide that demand stimulation is only possible by lowering prices. In order to keep margins at a satisfactory level in such a situation, the significant changes in sales channels, price management, pricing mechanisms and promotions are needed [4]. They are the following:…”
Section: S Ect Io N I I E Nt R Ep Rene U Rs Hi P T Ra De and Service S Ecto Rmentioning
confidence: 99%
“…These include the membership fee of video playback platforms and the bundled price of e-book reading devices [7][8][9][10]. Kort et al [11] found that many online sellers of digital content products are willing to launch their own mobile devices. In doing so, they can convert traditional wholesaler pricing into revenue-sharing contracts and increase their revenue.…”
Section: Introductionmentioning
confidence: 99%
“…Marketing is also an interesting aspect of supply chain research. Kort et al [13] discuss pricing decisions in dualchannel supply chain in the presence of optional contingent products. Yaghin [14] investigates a production planning problem in dyadic supply chain with multiperiod, multiproduct, multisite, and multi-sales channels.…”
Section: Introductionmentioning
confidence: 99%